2017
DOI: 10.1063/1.5003199
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Is a coarse-grained model for water sufficient to compute Kapitza conductance on non-polar surfaces?

Abstract: Coarse-grained models have increasingly been used in large-scale particle-based simulations. However, due to their lack of degrees of freedom, it is a priori unlikely that they straightforwardly represent thermal properties with the same accuracy as their atomistic counterparts. We take a first step in addressing the impact of liquid coarse-graining on interfacial heat conduction by showing that an atomistic and a coarse-grained model of water may yield similar values of the Kapitza conductance on few-layer gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…We do not report an application for cross spectra in this paper. However, we believe them to be helpful in areas such as interfacial heat transfer, which is proportional to the velocity force cross-correlations [42] and connected to the magnitude of the DoS [20]. An extension of DosCalc to calculate the velocity force cross-correlations would be easy to implement.…”
Section: Cross-spectramentioning
confidence: 99%
See 1 more Smart Citation
“…We do not report an application for cross spectra in this paper. However, we believe them to be helpful in areas such as interfacial heat transfer, which is proportional to the velocity force cross-correlations [42] and connected to the magnitude of the DoS [20]. An extension of DosCalc to calculate the velocity force cross-correlations would be easy to implement.…”
Section: Cross-spectramentioning
confidence: 99%
“…[19] Changes in the spectra of all-atom and coarse-grained water on a graphite surface are connected to heat transfer through the phase boundary. [20] For the quantification of rotational dynamics, autocorrelation functions of the angular velocity vector or orientational vectors are typically used. The latter are related to the rotational correlation time, which can be determined e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental investigation of molecular level heat transfer characteristics across the interfaces is challenging. Molecular dynamics (MD) simulation is one of the computer simulation techniques that is well suited to study the mechanism of nanoscale interfacial heat transfer as well as for evaluating the magnitude of thermal conductance. In our recent article, we observed that the thermal conductance at the interface between edge-on ideal crystal and single-layer graphene is two times higher than that for the interface between liquid heneicosane and graphene.…”
Section: Introductionmentioning
confidence: 99%
“…While there have been extensive studies to investigate thermal resistances at different types of interfaces by employing experimental analysis, analytical modeling, and numerical simulations, , traditional experimental approaches become impractical at nanometer scales. Instead, molecular dynamics (MD) simulations can provide a sufficient means to investigate nanoscale interfacial physics from an atomistic perspective. , The use of MD simulations enables the detailed calculations of thermophysical characteristics across individual phases and interfaces. The solid–liquid interfaces are reported with the focus on the surface morphological information, chemistry and roughness, nanofilm thickness, molecule packing levels, or their wettability, while the solid–liquid interfaces are influenced by phonon scattering mismatches. It has been reported that thermal resistances at solid–liquid interfaces for thin liquid films in the range of nanometers are comparable to those at solid–solid interfaces. , The majority of the previous studies has merely focused on the thermal transport between a solid and liquid without phase change. , …”
Section: Introductionmentioning
confidence: 99%
“…47−50 It has been reported that thermal resistances at solid−liquid interfaces for thin liquid films in the range of nanometers are comparable to those at solid−solid interfaces. 51,52 The majority of the previous studies has merely focused on the thermal transport between a solid and liquid without phase change. 49,53−55 The solid−liquid interfacial resistances have drawn attention during phase change phenomena.…”
Section: ■ Introductionmentioning
confidence: 99%